DIAGNOSTIC ACCURACY OF INDIRECT LARYNGOSCOPY AND X-RAY NECK IN THE DIAGNOSIS OF FISH BONE IMPACTION IN UPPER AERO DIGESTIVE TRACT: Diagnosis of Fish Bone Impaction - Kundi, Nasir Akram; Mehmood, Talat (Pakistan Armed Forces Medical Journal, 2015)
Objective: This study was aimed at finding the validity of indirect laryngoscopy (IDL) and neck X-Rays in the diagnosis of fish bone impaction.Study Design: Validation study.Place and Duration of Study: CMH Nowshera from August 2012 to February 2013.Material and Methods: A total of 50 patients were selected by consecutive sampling presenting with history of fishbone impaction in aerodigestive tract. IDL examination and neck X-rays were performed and findings were recorded. Those with no fishbone on both the investigations were discharged from hospital with follow up after 03 days. Those with fishbone detected on either of investigations underwent removal. Fishbone easily approachable were removed under local anaesthesia with foreceps and in others Endoscopy (Direct laryngoscopy or Oesophagoscopy) was performed under General Anaesthesia.  Sensitivities and specificities of both the modalities were calculated using standard 2/2 Table. ROC curve analysis was carried out and significance level p < 0.05 was taken as significant.  Results: In 20 patients no fishbone was found, 26 patients were diagnosed on IDL and in 04 patients fishbone was detected by neck X-Rays. Most common site for fishbone impaction was pharyngeal tonsil. In 22 patients fishbone was removed with foreceps and in 08 patients endoscopy was performed. Diagnostic accuracy for IDL 86% and Neck X-Rays 48% was calculated. ROC curve analysis revealed AUC for IDL 0.933 and Significance level (P) as